Risk factors and outcomes of infants with necrotizing enterocolitis: a case-control study - Kamanga, Noela H. B.; Thomas, Reenu; Thandrayen, Kebashni; Velaphi, Sithembiso C. (Frontiers in Pediatrics, 2025)
IntroductionNecrotizing enterocolitis (NEC) is a condition associated with high mortality and morbidity. Its pathogenesis is linked to intestinal immaturity, inflammation, and enteral feeding. Identifying risk factors for the development of NEC and its mortality can inform targeted preventative strategies.AimThe aim of the study was to assess the incidence, characteristics, risk factors, and outcomes of infants diagnosed with NEC in a large tertiary neonatal unit in South Africa.MethodsA prospective case-control study was conducted from May 2022 to December 2024 at Chris Hani Baragwanath Academic Hospital. Infants diagnosed with definite NEC (modified Bell's stage 2 or 3) were included as cases. Each case was matched with 1–2 controls by weight and postnatal age. The demographic characteristics, laboratory findings, management, and outcomes of cases and controls were reviewed. Comparisons were performed between cases and controls, and between survivors and non-survivors amongst the cases using univariate and multivariate logistic regression analyses.ResultsThere were 167 cases of NEC enrolled. The incidence rate of definite NEC was 3.4/1,000 live births, comprising 1.4% and 4.0% of all neonatal admissions and very low birth weight infants, respectively. The median gestational age, birth weight, and postnatal age of cases were 31 weeks, 1,455 g, and 8.5 days, respectively. Cases were more likely to have been formula fed (OR: 2.00; 95% CI 1.20–3.33), have been previously exposed to a longer duration of antibiotics (OR: 1.26; 95% CI 1.14–1.40), and to have received a blood transfusion (OR: 27.4; 95% CI 2.09–359), and less likely to have reached full feeds in a shorter time (OR: 0.88; 95% CI 0.80–0.95). In total, 91 cases (54.5%) had culture-confirmed sepsis. The mortality rate was 49.7%, with ventilation and hypotension predictors of mortality.ConclusionThere was a high incidence of definite NEC, with associated high mortality, mainly in infants who were ventilated and hypotensive. Factors associated with NEC were formula feeding, longer duration of antibiotics, and prior blood transfusion.